Eksplorasi Etnomatematika Terhadap Arsitektur Masjid Majapahit Al Hikam Pekalongan - Tarisa Shinta Ihsani; Isnaini Rosidah; Dilla Setiani; Ahmad Faridh Ricky Fahmi (JUMAT: Jurnal Matematika, 2023)
Ethnomathematics is a branch of science that observes how mathematics is connected to the culture of a society. This research aims to identify and explain various forms of mathematical geometry present in the architectural design of the Majapahit Al Hikam Mosque in Pekalongan, with the goal of mathematics education. The research method is qualitative with an ethnographic approach, where the researcher acts as the primary instrument gathering information through observation, interviews, and documentation. The data analysis process consists of three stages: data reduction, data presentation, and drawing conclusions. Historical information about the Majapahit Al Hikam Mosque in Pekalongan was obtained through interviews and literature studies. The research results indicate that the architecture of the Majapahit Al Hikam Mosque in Pekalongan is linked to mathematical geometry concepts such as triangles, hexagons, rectangles, circles, blocks, cylinders, pyramids, reflections, rotations, and so on. This study is a part of ethnomathematics and serves as an alternative tool for learning mathematics, with the hope of being applicable in contextual learning, providing concrete examples of the application of mathematical concepts in everyday life.